2013
DOI: 10.1007/s00535-013-0911-1
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus is associated with the fibrosis severity in patients with nonalcoholic fatty liver disease in a large retrospective cohort of Japanese patients

Abstract: DM appeared to be a significant risk factor for advanced fibrosis in patients with NAFLD, and would therefore need to be properly managed to prevent the progression of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(123 citation statements)
references
References 39 publications
6
114
0
3
Order By: Relevance
“…In chronic hepatitis B, presence of DM could prevent fibrosis regression after antiviral therapy for chronic hepatitis B and also associated with progression of liver fibrosis and complications of liver cirrhosis. 3436 DM appears to be a significant factor of advanced liver fibrosis in NAFLD and chronic hepatitis C. 37,38 Taking together of lines of evidence indicated that DM seems to play an universal role in liver fibrosis progression either in general population or in coexisting chronic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic hepatitis B, presence of DM could prevent fibrosis regression after antiviral therapy for chronic hepatitis B and also associated with progression of liver fibrosis and complications of liver cirrhosis. 3436 DM appears to be a significant factor of advanced liver fibrosis in NAFLD and chronic hepatitis C. 37,38 Taking together of lines of evidence indicated that DM seems to play an universal role in liver fibrosis progression either in general population or in coexisting chronic liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance and obesity are closely related to the development and progression of NAFLD [6]. The most common complications of NAFLD are type 2 diabetes mellitus and impaired glucose tolerance [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we discuss the genetic factors implicated in steatosis, steatohepatitis, fibrosis progression, cirrhosis, and HCC in NAFLD patients. (Table 1) About half of Japanese patients with NAFLD have hyperlipidemia [7]. Lipid metabolism in the liver and peripheral tissue plays a critical role in NAFLD onset and progression.…”
Section: Introductionmentioning
confidence: 99%